Female passengers' perception on the service quality of public bus services: an exploratory study on Dhaka City, Bangladesh. (4th September 2019) - Rouf, Khadija Bint Abdur; Hossain, Dewan Mahboob; Hossain, Moinul
There is a difference in travel pattern between men and women due to their varying trip purpose and access to transportation facilities. Women travellers these days generate a substantial number of trips on regular basis even in the developing world where they enjoy less freedom. Hence, it is important to ensure that the available public transportation system can attract female travellers. This study combines and customises two well-known service quality assessment models - SERVQUAL and RESCA to explore the perceptions of female university students regarding the public bus services in Dhaka City, Bangladesh. The study is qualitative in nature and follows an interpretive paradigm involving interviews of 20 female university students. Their perceptions are evaluated based on seven attributes: 1) reliability; 2) comfort; 3) service; 4) responsiveness and empathy; 5) safety and security; 6) affordability; 7) vehicle access. The findings postulate that the existing public bus service is unpleasant for both the genders. However, the situation is more hostile for the female passengers. Several interesting suggestions also came forward. It is expected that these recommendations shall help improving the public bus service for female users.